PENGGUNAAN MEDIA SPINNING WHEEL TERINTEGRASI MODEL PEMBELAJARAN TGT DALAM PEMBELAJARAN MEMBACA PERMULAAN PESERTA DIDIK KELAS 1 SD NEGERI LAMPEUNEURUT ACEH BESAR - Siti Rahmawati; Intan Safiah; Hasniyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by differences in beginning reading abilities among firstgrade students at SD Negeri Lampeuneurut Aceh Besar, where some students were able to read fluently while others were still recognizing letters, syllables, or simple words. This condition indicates the need for appropriate instructional media and learning models to improve students’ abilities and participation. The study aimed todescribe students’ learning activities and their beginning reading test results through the use of the spinning wheel media integrated with the Teams Games Tournament (TGT) learning model. This research employed a descriptive qualitative approach, with data collected through observation and beginning reading tests. The results showed that the implementation of the spinning wheel media integrated with the TGT model increased students’ learning activities and demonstrated positive development in reading accuracy, pronunciation, intonation, fluency, and voice clarity. Thus, the media and learning model had a positive impact on the process and outcomes of beginning reading instruction